Association between quality of sleep and academic performance: evidence from undergraduate students from Sabah, Malaysia - Balan Rathakrishnan; Soon Singh Bikar Singh; Mohd Fahmi Ghazali; Azizi Yahaya; Noor Hassline Mohammed; Mohammad Rahim Kamaluddin (Bahawalpur: Human Resource Management Academic Research Society, 2021)
Sleeping patterns have been one of the most essential aspects of one’s lives, which also contribute to memorization and learning. However, undergraduate students seem to underestimate the importance of sleep by skipping a night of sleep to spend time on other works. As a result, their academic performance is affected due to poor sleep quality. Thus, this study was conducted to examine the relationship between quality of sleep and academic performance among undergraduate students in Sabah. This study comprised a convenience sample of 407 undergraduate students aged 18-26 as participants. The data were obtained through a questionnaire survey, where participants were required to provide demographic information, cumulative grade point average (CGPA) and select Sleep Quality Scale (SQS). The findings show a positive correlation, r=0.342, p<0.05 shows there is a positive relationship between the quality of sleep and academic performance among undergraduate students in Sabah. Thus, students need to focus on their sleep quality in order to improve their quality of life overall as adequate sleep leads to the physical health and well-being of a student